2020
DOI: 10.18438/eblip29634
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Reference Narrative: Assessing Student Learning in Research Consultations

Abstract: Abstract Objective – As reference services continue to evolve, libraries must make evidence based decisions about their services. This study seeks to determine the value of reference services in relation to student learning acquired during research consultations, by soliciting students’ and librarians’ perceptions of consultation success and examining the degree of alignment between them. Methods – The alignment of students’ learning outcomes (reported skills and knowledge acquired) with librarians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Regardless of their degree of standardization, data collection and assessment projects focused on reference services in academic libraries tend to center patron service needs ( Scales et al, 2015 ), student experiences and satisfaction ( Murgai, 2012 ; Reiter & Cole, 2019 ; Rogers & Carrier, 2017 ), or student learning outcomes ( Bradley et al, 2020 ; Maddox & Stanfield, 2020 ; Miller, 2018 ; Newton & Feinberg, 2020 ; Sikora & Fournier, 2016 ). The effects on librarians of providing these services and the use of reference statistics in predicting or assessing librarian workload and effort are comparatively little studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regardless of their degree of standardization, data collection and assessment projects focused on reference services in academic libraries tend to center patron service needs ( Scales et al, 2015 ), student experiences and satisfaction ( Murgai, 2012 ; Reiter & Cole, 2019 ; Rogers & Carrier, 2017 ), or student learning outcomes ( Bradley et al, 2020 ; Maddox & Stanfield, 2020 ; Miller, 2018 ; Newton & Feinberg, 2020 ; Sikora & Fournier, 2016 ). The effects on librarians of providing these services and the use of reference statistics in predicting or assessing librarian workload and effort are comparatively little studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding aligns with the findings of studies exploring both recorded consultations in a medical setting (Rieger et al , 2018) and with broader findings regarding IRCs (Stapleton et al , 2020). It should be noted however that numerous studies on non-recorded IRCS have reported high levels of usefulness of the intervention (Magi and Mardeusz, 2013a; Butler and Byrd, 2016; Rogers and Carrier, 2017; Bezet et al , 2018; Sikora et al , 2019; Bradley et al , 2020). This study was not a side-by-side comparison of recorded and non-recorded IRCS and thus cannot demonstrate if the addition of recording further improves the positive perception students report of IRCs.…”
Section: Discussionmentioning
confidence: 98%
“…Bezet et al (2018) reported skills acquisition from IRCs including search technique, controlled vocabulary use and database functionality. Bradley et al, (2020) reported participants' increased application of research skills but these were not specified. While these studies made reference to students (perceived) increase in research skills, neither investigated how students integrate knowledge gained in an IRC into research activities or how knowledge transfer occurs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations